INTERNET OF THINGS BASED SENSIBLE AND SECURE HOME AUTOMATION SYSTEM - Singhal, Pulkit; Tiwari, Akshat; Prakash, M. (International Journal of Psychosocial Rehabilitation, 2020)
— In the past few years, along with the advances in technology, the home automation systems have begun to provide additional functions and been additional subtle. Compared to the past, remotely governable home automation systems became less expensive and aren't luxurious anymore; thence additional and additional individuals today use home automation systems to form their lives easier. This is precisely what this project will, victimization Associate in Nursing app on our phone we are able to management all electrical instrumentality in our home. This can be an easy project created with the aim to regulate electrical appliances without switches, and incorporating a smart app to accomplish this, the medium are going to be the web. The setup incorporates a Raspberry Pi. The top result is going to be a system wherever you'll be able to operate the appliances via phone. The core objective of this work is to develop sensible and secure home (SSH) victimization Internet of Things (IoT) devices which might be controlled and monitored victimization automation smart phone.